INFLUENCE OF THE DEFORMATION PROCESSES AND STRUCTURAL-PHASE TRANSFORMATIONS ON THE WEARABILITY OF CONTACT - Мікосянчик, Оксана Олександрівна; Токарук, Віталій Володимирович; Мнацаканов, Рудольф Георгійович; Занько, Сергій Миколайович; Жосан, Олександр Юрійович (Problems of Friction and Wear, 2021)
The analysis of diffractograms of metal surface layers under friction in the conditions of rolling with various degree of sliding has been carried out. The mechanisms of strengthening of contact surfaces as a result of their structural adaptation at friction have been considered. It has been identified that an increase in degree of sliding leads to intensification of diffusion processes, increase of temperature in the zone of frictional contact, increase of shear rate gradient, which supports the formation of carbide and austenitic phases, and amorphization of near-surface metal layers. The possibility of the phase transformations during friction including the formation of austenite due to secondary hardening is realized under conditions that include both local heating to temperatures above critical and cooling to room temperatures at high speed in areas of microcontact, and reduction of critical points under deformation. The formation of a fine structure under increasing slippage due to the localization of maximum shear stresses in the near-surface layers of the metal also facilitates structural transformations: the homogenization of austenite, dissolution and release of carbides, intense diffusion in micro-volumes, etc. Herewith, the display lines (α-Fe) are shifted towards small angles, which mean an increase in lattice period, due to the dissolution of impurities in it (carbon, oxygen, nitrogen). The depth of the amorphous deformed metal layer of the lagging surface under conditions of slipping 3, 20 and 40% is respectively 40 - 50 μm, 30 - 40 μm and 100 - 300 μm. The influence of structural-deformation changes in surface and near-surface layers of contact surfaces on their wear resistance has been explored. The highest anti-wear properties are displayed in contact surfaces operating in rolling conditions with slipping of 20%, for which, on average, the reduction of linear wear of both leading and lagging surfaces by 30%, in comparison with the studied samples with slipping 3 and 40 %.